Comparative cohort study of post-acute COVID-19 infection with a nested, randomized controlled trial of ivabradine for those with postural orthostatic tachycardia syndrome (the COVIVA study) - David Saunders; Thomas B. Arnold; Thomas B. Arnold; Thomas B. Arnold; Jason M. Lavender; Jason M. Lavender; Jason M. Lavender; Daoqin Bi; Daoqin Bi; Daoqin Bi; Karl Alcover; Lydia D. Hellwig; et al. (Frontiers in Neurology, 2025)
BackgroundSignificant clinical similarities have been observed between the recently described “Long-Haul” COVID-19 (LHC) syndrome, Postural Orthostatic Tachycardia Syndrome (POTS) and Inappropriate Sinus Tachycardia (IST). Shared symptoms include light-headedness, palpitations, tremulousness, generalized weakness, blurred vision, chest pain, dyspnea, “brain-fog,” and fatigue. Ivabradine is a selective sinoatrial node blocker FDA-approved for management of tachycardia associated with stable angina and heart failure not fully managed by beta blockers. In our study we aim to identify risk factors underlying LHC, as well as the effectiveness of ivabradine in controlling heart rate dysregulations and POTS/IST related symptoms.Methods/designA detailed prospective phenotypic evaluation combined with multi-omic analysis of 200 LHC volunteers will be conducted to identify risk factors for autonomic dysfunction. A comparator group of 50 volunteers with documented COVID-19 but without LHC will be enrolled to better understand the risk factors for LHC and autonomic dysfunction. Those in the cohort who meet diagnostic criteria for POTS or IST will be included in a nested prospective, randomized, placebo-controlled trial to assess the impact of ivabradine on symptoms and heart rate, assessed non-invasively based on physiologic response and ambulatory electrocardiogram. Additionally, studies on catecholamine production, mast cell and basophil degranulation, inflammatory biomarkers, and indicators of metabolic dysfunction will be measured to potentially provide molecular classification and mechanistic insights.DiscussionOptimal therapies for dysautonomia, particularly associated with LHC, have yet to be defined. In the present study, ivabradine, one of numerous proposed interventions, will be systematically evaluated for therapeutic potential in LHC-associated POTS and IST. Additionally, this study will further refine the characteristics of the LHC-associated POTS/IST phenotype, genotype and transcriptional profile, including immunologic and multi-omic analysis of persistent immune activation and dysregulation. The study will also explore and identify potential endotheliopathy and abnormalities of the clotting cascade.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT05481177.